Oxygen-Dependent Blood Processes in Beck's Sarcoidosis - N. V. Glutkina; V. V. Zinchuk (Туберкулез и болезни лёгких)
The objective: to assess the state of oxygen-dependent blood processes in patients with Beck's sarcoidosis.Subjects and Methods. Parameters of blood oxygen transport function and free radical lipid oxidation, as well as the content of nitrogen monoxide and hydrogen sulfide gas transmitters were assessed in the blood of 75 patients (41 women; 34 men) with Beck's sarcoidosis, stage 2 (the pulmonary mediastinal form).Results. In the pulmonary mediastinal form of sarcoidosis versus healthy individuals, there was a decrease in the degree of blood oxygen saturation from 65.4 (60.6; 67.8) to 41.50 (36.0; 49.8), p < 0.05, %, partial oxygen pressure from 40.0 (38.0; 47.0) to 23.0 (18.3; 29.0) mmHg, p < 0.05, and blood pH increased. A decrease in the index of hemoglobin affinity to oxygen p50real (26.80 (24.70; 31.40), p < 0.05, versus healthy individuals 28.2 (27.9; 29.1) mmHg) was revealed. The level of diene conjugates increased in plasma by 86.4% (p < 0.05) and malondialdehyde increased in erythrocytes by 139.2% (p < 0.05), while the following parameters decreased: α-tocopherol (by 42.7 %, p < 0.05), retinol (by 41.9%, p < 0.05), reduced glutathione (by 30.4%, p < 0.05), and ceruloplasmin (by 22.3%, p < 0.05) in plasma. There was an increase in the concentration of nitrogen monoxide (from 15.42 (14.48; 17.71) to 17.09 (7.04; 25.09), mmol/L) and a decrease in hydrogen sulfide (from 29.01 (25.21; 37.03) to 13.08 (8.63; 20.46), mmol/L) in the blood in case of this pathology.Conclusion. There is a deterioration in the blood oxygen-binding properties in patients with Beck's sarcoidosis, stage 2, and as a consequence, tissue needs in oxygen are not adequately provided by blood circulation. There is an increase in the concentration of nitrogen monoxide and a decrease in hydrogen sulfide, which affects the oxygen transport function of blood which may be important for ensuring the processes of oxygen transfer to tissues. In this pathology, activation of lipid peroxidation and a decrease in the level of antioxidant protection factors of blood were revealed which might be important for the genesis of this disease.